Made in Latin America : open access, scholarly journals, and regional innovations - Aguado López, Eduardo; Alonso Gamboa, José Octavio; Alperin, Juan Pablo; Alperin, Juan Pablo; Amorim, Keyla Mafalda de Oliveira; Ávila, Nathalia da Silva; Bongiovani, Paola; Cetto, Ana María; Degani; Fischman, Gustavo; Fischman, Gustavo; Gómez, Nancy D.; et al. (CLACSO, 2021)
Latin America distinguishes itself from other regions of the world by considering the scientific information as a common good. All the above initiatives are publicly funded and managed by the same academic community that publishes scientific journals, unlike in Europe and the United States, where much of the scientific communication — mainly journals — has been outsourced and commercialized. The book presented here provides the results of exploratory research and different perspectives on achievements, detected problems and challenges the region will be facing in the future, in relation to access, visibility, and scientific and social impact of research published in journals in Latin America, the evaluation of these journals by assessment systems and incentives for academic and scientific careers in the region.